Використання саморіжучих заклепок в конструкції кузова перонних автобусів для аеропортів - Нечипорук, Микола; Воробйов, Юрій (Видавництво Львівської політехніки, 2018)
The article describes the order of carrying out and the results of experimental studies and numerical simulation of pulsed riveting with a manual pneumatic impulse tool of steel self-pierce rivets in the construction of the body of the bus for airports.
Using self-pierce rivets in the structure of the body of the platformbus for airports
Keywords: 629.33.02; 621.88; 621.9.044